A solid-state electrolyte, battery

CN122907727APending Publication Date: 2026-10-13SHENZHEN HAODYNE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611304864.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明针对现有的固态电解质离子电导率低、界面相容性差和力学强度低的问题,本发明提供一种固态电解质、电池

Benefits of technology

[0016]本申请中,黄原胶具有刚性螺旋链,为多糖基体提供骨架支撑,魔芋葡甘聚糖具有柔性无规线团构象,提供为多糖基体柔性填充,两者在分子尺度上互补,形成致密互穿三维网络,所述磷酸二酯基团作为黄原胶和魔芋葡甘聚糖分子链共价交联位点,构建三维网络结构,磷酸单酯基团携带游离磷酸基团作为锂离子解离传输位点,可促进锂盐的解离,增加自由离子浓度,提高含有多糖基体的固态电解质的离子电导率。磷酸二酯基团作为多糖分子链共价交联位点构建三维网络结构,磷酸单酯基团携带游离磷酸基团作为锂离子解离传输位点,可促进锂盐的解离,增加自由离子浓度,提高固态电解质的离子电导率。通过限定磷酸单酯基团和磷酸二酯基团的摩尔比区间为1~3:1,磷酸二酯基团作为共价交联点可提供足够的力学强度,磷酸单酯作为锂离子解离位点可保证高效离子传输,实现两类性能的协同优化。多糖基体可生物降解、生物相容性好,固态电解质中使用多糖基体,可保证固态电解质的环境友好性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

In view of the problems of low solid-state electrolyte ion conductivity and low mechanical strength of the existing battery, the application provides a solid-state electrolyte and a battery.The solid-state electrolyte comprises a polysaccharide base body, the polysaccharide base body comprises xanthan gum and konjac glucomannan, the polysaccharide base body further comprises a modified group, the modified group comprises a phosphoric monoester group and a phosphoric diester group, and the molar ratio of the phosphoric monoester group and the phosphoric diester group is (1-3):1.The phosphoric diester group in the solid-state electrolyte provided by the application is used as a covalent crosslinking site of a polysaccharide molecular chain to construct a three-dimensional network structure, and the phosphoric monoester group carries a free phosphoric acid group as a lithium ion dissociation and transmission site, so that the dissociation of lithium salt can be promoted, and the ion conductivity of the solid-state electrolyte can be improved.The molar ratio of the phosphoric monoester group and the phosphoric diester group is limited to 1-3:1, the phosphoric diester group can provide sufficient mechanical strength as a covalent crosslinking site, and the phosphoric monoester group can ensure efficient ion transmission as a lithium ion dissociation site, so that the synergistic optimization of the two types of performance can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of secondary battery technology, specifically relating to a solid electrolyte and a battery. Background Technology

[0002] Since their commercialization, lithium-ion batteries have been widely used in portable electronic devices and electric vehicles. Unlike traditional liquid lithium-ion batteries, all-solid-state lithium batteries have advantages such as high specific energy, high safety performance, and long cycle life, and have become a research and development hotspot in the field of new chemical batteries in recent years.

[0003] Existing solid electrolytes mainly include three major systems: inorganic ceramics, polymers, and composites. Among them, inorganic ceramic electrolytes have high ionic conductivity, but they are brittle, have poor processability, poor electrode interface contact, and high interfacial impedance, making large-scale preparation difficult. Polymer electrolytes, represented by polyethylene oxide, have excellent processing and flexibility properties, but they have low room temperature ionic conductivity and insufficient mechanical strength, making it difficult to effectively suppress lithium dendrite growth and balance electrochemical performance and cycle safety. Composite electrolytes can combine the advantages of both types of materials, but they suffer from complex preparation processes and high costs.

[0004] Therefore, there is an urgent need for a solid electrolyte that combines high ionic conductivity and high mechanical strength. Summary of the Invention

[0005] This invention addresses the problems of low ionic conductivity, poor interfacial compatibility, and low mechanical strength of existing solid electrolytes by providing a solid electrolyte and battery.

[0006] To solve the above-mentioned technical problems, the present invention provides a solid electrolyte comprising a polysaccharide matrix, wherein the polysaccharide matrix comprises xanthan gum and konjac glucomannan, and the polysaccharide matrix further comprises modifying groups, wherein the modifying groups comprise phosphate monoester groups and phosphate diester groups, and the molar ratio of the phosphate monoester groups and phosphate diester groups is (1~3):1.

[0007] Preferably, the polysaccharide matrix is ​​prepared from a raw material composition including xanthan gum, konjac glucomannan and a phosphorylation reaction solution, wherein the pH of the phosphorylation reaction solution is 4-5.5.

[0008] Preferably, the phosphorylation reaction solution comprises phosphate and citric acid.

[0009] Preferably, the phosphate includes at least one of disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, sodium hexametaphosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

[0010] Preferably, the mass ratio of xanthan gum to konjac glucomannan is 1:(1.2~1.8).

[0011] Preferably, the molar ratio of the polysaccharide matrix to the modified group is 1:(0.15-0.30).

[0012] Preferably, the polysaccharide matrix further includes functional polysaccharides, which include at least one of sodium alginate, carboxymethyl cellulose, chitosan, guar gum, and hyaluronic acid.

[0013] Preferably, the total mass ratio of xanthan gum and konjac glucomannan to the mass ratio of the functional polysaccharide is (60~95):(5~40).

[0014] Preferably, the solid electrolyte further includes lithium salt, functional additives and residual solvent, wherein the functional additives include at least one of inorganic fillers, interface modifiers and film-forming additives; The mass ratio of the polysaccharide matrix, lithium salt, inorganic filler, interface modifier, film-forming additive and residual solvent is (30~45):(15~25):(15~25):(5~10):(10~18):(5~10).

[0015] Secondly, this application provides a battery including a solid electrolyte as described above.

[0016] In this application, xanthan gum has rigid helical chains, providing skeletal support for the polysaccharide matrix, while konjac glucomannan has a flexible random coil conformation, providing flexible filling for the polysaccharide matrix. The two are complementary at the molecular scale, forming a dense, interpenetrating three-dimensional network. The phosphate diester groups serve as covalent cross-linking sites for the xanthan gum and konjac glucomannan molecular chains, constructing the three-dimensional network structure. The phosphate monoester groups, carrying free phosphate groups, serve as lithium-ion dissociation transport sites, promoting lithium salt dissociation, increasing free ion concentration, and improving the ionic conductivity of the solid electrolyte containing the polysaccharide matrix. The phosphate diester groups, as covalent cross-linking sites for the polysaccharide molecular chains, construct the three-dimensional network structure. The phosphate monoester groups, carrying free phosphate groups, serve as lithium-ion dissociation transport sites, promoting lithium salt dissociation, increasing free ion concentration, and improving the ionic conductivity of the solid electrolyte. By limiting the molar ratio of phosphate monoester groups to phosphate diester groups to 1–3:1, the phosphate diester groups, acting as covalent crosslinking points, provide sufficient mechanical strength, while the phosphate monoesters, acting as lithium-ion dissociation sites, ensure efficient ion transport, achieving synergistic optimization of both properties. The polysaccharide matrix is ​​biodegradable and biocompatible; using a polysaccharide matrix in solid-state electrolytes ensures their environmental friendliness. Detailed Implementation

[0017] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0018] One embodiment of this application provides a solid electrolyte comprising a polysaccharide matrix, the polysaccharide matrix comprising xanthan gum (XG) and konjac glucomannan (KGM), the polysaccharide matrix further comprising modifying groups, the modifying groups comprising phosphate monoester groups (MPE) and phosphate diester groups (DPE), the molar ratio of the phosphate monoester groups to the phosphate diester groups being (1~3):1.

[0019] From the perspective of molecular and esterification reaction kinetics, XG consists of a rigid helical molecular chain, while KGM consists of a flexible random molecular chain. Both have hydroxyl groups on their molecular chain surfaces, allowing them to spontaneously build physically interpenetrating three-dimensional networks using only intermolecular hydrogen bonds. However, pure hydrogen bonds are weak intermolecular forces, resulting in extremely low cross-linking density in the original network and insufficient electrolyte mechanical modulus. Phosphate and polysaccharide hydroxyl groups undergo two competing reversible esterification reactions: one is diesterization to generate DPE, where a single phosphate molecule simultaneously bonds to the hydroxyl groups of two polysaccharide molecular chains, forming covalent cross-linking nodes across molecular chains, significantly increasing the cross-linking density of the polysaccharide network and the tensile modulus of the membrane; the other is monoesterization to generate MPE, where a single phosphate molecule binds only to the hydroxyl groups of a single polysaccharide molecular chain, exposing a large number of free -PO3H2 polar groups on the side chains. These groups can act as Li + The polysaccharide matrix provides dissociation sites and facilitates rapid lithium-ion migration via continuous polar phosphate side chains. Its biodegradability and good biocompatibility ensure the environmental friendliness of solid-state electrolytes.

[0020] In this embodiment, by limiting the molar ratio of phosphate monoester groups and phosphate diester groups to a range of 1 to 3:1, the phosphate diester groups, as covalent crosslinking points, can provide sufficient mechanical strength, while the phosphate monoesters, as lithium ion dissociation sites, can ensure efficient ion transport, thus achieving synergistic optimization of the two types of performance.

[0021] When the molar ratio is less than 1:1, the proportion of monophosphate groups in the system is too high or the number of covalent cross-linking sites of phosphate diester groups is insufficient. The three-dimensional network structure of the polysaccharide matrix is ​​loose, and it cannot rely on physical barriers to prevent lithium dendrite puncture growth. At the same time, the molecular chain slippage phenomenon is severe, and the electrolyte membrane is prone to damage during long-term battery cycling, and the interfacial impedance between the electrode and the electrolyte continues to rise. The higher the proportion of phosphate diester groups and the greater the cross-linking density, the higher the tensile strength of the solid electrolyte. High tensile strength can effectively prevent lithium dendrite puncture growth and improve battery safety. However, when the molar ratio is higher than 3:1, the proportion of phosphate diester matrix is ​​too high, the covalent cross-linking density is too large, the movement space of polysaccharide molecular chains is severely restricted, the lithium ion transport channels are blocked by cross-linking nodes, and the ionic conductivity of the solid electrolyte is reduced.

[0022] The molar ratio of phosphate monoester groups to phosphate diester groups includes, but is not limited to, 1.0:1, 1.1:1, 1.2:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.9:1, 2.0:1, 2.1:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.8:1, 2.9:1, or 3.0:1.

[0023] In some embodiments, the polysaccharide matrix is ​​prepared from a raw material composition comprising xanthan gum, konjac glucomannan, and a phosphorylation reaction solution, wherein the pH of the phosphorylation reaction solution is 4-5.5. When the pH of the phosphorylation reaction solution is <4, the phosphate mainly exists in the form of H3PO4, which inhibits the esterification reaction between the phosphate groups and the polysaccharide hydroxyl groups, resulting in insufficient cross-linking, decreased mechanical strength, and difficulty in effectively suppressing lithium dendrites. When the pH is >5.5, the HPO4 in the phosphate... 2- and PO4 3- As the proportion increases, the phosphorylation reaction activity increases, but the reaction rate becomes too fast, leading to excessive diesterization and cross-linking. This restricts molecular chain movement, blocks ion transport channels, and reduces ionic conductivity. The competitive balance between the two esterification reactions can be controlled by adjusting the pH of the phosphorylation reaction solution.

[0024] In some embodiments, the phosphorylation reaction solution comprises phosphate and citric acid. Citric acid, acting as a pH buffer and complexing agent, can precisely regulate the active sites of the phosphorylation reaction, achieving directional control of the ratio of the two phosphate ester groups.

[0025] In some embodiments, the phosphate includes at least one of disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, sodium hexametaphosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

[0026] In some embodiments, the mass ratio of xanthan gum to konjac glucomannan is 1:(1.2~1.8).

[0027] When the mass ratio of xanthan gum to konjac glucomannan is higher than 1:1.2, the rigid component of xanthan gum is excessive, increasing the brittleness of the formed hydrogel and decreasing the elongation at break. When the mass ratio of xanthan gum to konjac glucomannan is lower than 1:1.8, the flexible component of konjac glucomannan is excessive, resulting in a lack of hydrogen bond network support, limited subsequent phosphorylation reinforcement effect, and reduced lithium dendrite suppression strength.

[0028] When the mass ratio of xanthan gum to konjac glucomannan is in the range of 1:(1.2~1.8), the spatial conformation of the rigid xanthan gum molecular chain and the flexible konjac glucomannan molecular chain is highly matched. They spontaneously form a dense, crack-free interpenetrating hydrogel matrix by means of intermolecular hydrogen bonds. The formed hydrogel has both basic flexibility and mechanical support, providing a high-quality precursor for subsequent directional phosphorylation covalent crosslinking modification.

[0029] The mass ratio of xanthan gum to konjac glucomannan includes, but is not limited to, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7 or 1:1.8.

[0030] In some embodiments, the molar ratio of the polysaccharide matrix to the modified groups is 1:(0.15–0.30). By limiting the molar ratio of the polysaccharide matrix to the modified groups within the above range, precise quantitative matching of the polysaccharide three-dimensional network framework and the phosphorylation modified groups is achieved, taking into account the integrity of the matrix structure, the strength of covalent crosslinking, and the density of lithium-ion active sites. This forms a bilayer synergistic regulatory system with the molar ratio of phosphate monoester groups and phosphate diester groups, further broadening the performance regulation window of solid electrolytes.

[0031] Specifically, the molar ratio of the polysaccharide matrix to the modified group includes, but is not limited to, 1:0.15, 1:0.17, 1:0.19, 1:21, 1:0.23, 1:0.25, 1:0.27, 1:0.29 or 1:0.3.

[0032] In some embodiments, the polysaccharide matrix further includes functional polysaccharides, which include at least one of sodium alginate (SA), carboxymethyl cellulose (CMC), chitosan (CS), guar gum (GG), and hyaluronic acid (HA). Sodium alginate and carboxymethyl cellulose can fill the micropores inside the polysaccharide network, improving the film-forming properties and mechanical strength of the electrolyte; chitosan and guar gum can enrich the active sites of the molecular chains, thereby increasing the active sites for lithium salt dissociation and improving ionic conductivity; hyaluronic acid can improve interfacial compatibility and reduce interfacial impedance. The polysaccharide matrix of the solid electrolyte can contain any single functional polysaccharide, or multiple functional polysaccharides can be used in combination. Combinations of multiple functional polysaccharides can superimpose multiple modification gains, simultaneously enhancing the mechanical properties, ion conductivity, and interfacial compatibility of the solid electrolyte.

[0033] In some embodiments, the mass ratio of the total mass of xanthan gum and konjac glucomannan to the mass of the functional polysaccharide is (60~95):(5~40). That is, based on a polysaccharide matrix content of 100%, the total mass content of xanthan gum and konjac glucomannan is 60%~95%. The rigid helical molecular chains of xanthan gum and the flexible random molecular chains of konjac glucomannan possess a unique hydrogen bond matching structure. When their total mass ratio is 60~95 ​​parts, they can form a continuous and complete interpenetrating three-dimensional network framework within the polysaccharide matrix, improving the mechanical strength of the solid electrolyte. When the total mass ratio of xanthan gum and konjac glucomannan is less than 60 parts, the proportion of functional polysaccharides such as sodium alginate and chitosan is too high, which will destroy the unique hydrogen bond sites of xanthan gum and konjac glucomannan, partially damaging the network structure within the polysaccharide matrix and reducing the mechanical strength of the solid electrolyte. When the total mass of xanthan gum and konjac glucomannan is maintained at 60-95 parts, the functional polysaccharides only fill the gaps in the network as a modifying agent and do not destroy the basic continuous skeleton.

[0034] In the polysaccharide matrix, the mass ratio of the total mass of xanthan gum and konjac glucomannan to the mass of the functional polysaccharide includes, but is not limited to, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, and 95:5.

[0035] In some embodiments, the mass content of any one of sodium alginate, carboxymethyl cellulose, chitosan, guar gum, and hyaluronic acid in the polysaccharide matrix is ​​5% to 30%.

[0036] When the amount of a single functional polysaccharide added is less than 5%, the number of molecular chains is insufficient, and it is impossible to form a sufficient number of hydrogen bonds or ionic active sites, resulting in weak modification gains and no practical value. When the amount added is more than 30%, a large amount of functional polysaccharides dilute the mass ratio of xanthan gum and konjac glucomannan to the core backbone components, destroying part of the continuous interpenetrating network in the polysaccharide matrix, and reducing the mechanical strength of the solid electrolyte.

[0037] The mass content of any one of sodium alginate, carboxymethyl cellulose, chitosan, guar gum, and hyaluronic acid added to the polysaccharide matrix includes, but is not limited to, 5%, 6%, 7%, 9%, 10%, 11%, 13%, 15%, 16%, 17%, 19%, 21%, 23%, 24%, 25%, 27%, and 30%. When multiple functional polysaccharides are used in combination, the individual mass percentage of each functional polysaccharide shall not exceed 30%, and the total mass fraction of all functional polysaccharides shall not exceed 40%.

[0038] In some embodiments, the solid electrolyte further includes lithium salt, functional additives, and residual solvent, wherein the functional additives include at least one of inorganic fillers, interface modifiers, and film-forming additives.

[0039] The three types of functional additives possess independent molecular action mechanisms, while also exhibiting significant synergistic enhancement effects. The inorganic filler, being rigid particles, restricts polysaccharide chain slippage, reinforcing mechanical properties. The interface modifier polymerizes in situ on the lithium metal anode surface to form a uniform, flexible SEI passivation film, eliminating solid-solid interface voids and significantly reducing interfacial impedance. The film-forming additive preferentially decomposes during battery charge-discharge cycles, generating a dense passivation film containing F and S, isolating lithium salt, solvent, and electrode side reactions, thus extending cycle life. Residual solvent refers to the portion remaining after drying of the solvent added during solid electrolyte preparation.

[0040] Single-component additives optimize only a single property, while the combination of three types of additives forms a complete synergistic system. Inorganic fillers provide the bulk mechanical framework and bulk ion channels; interface modifiers optimize the static interface adhesion at room temperature; and film-forming additives improve the interface stability during high and low temperature cycling. The combination of the three simultaneously achieves the three major advantages of high strength, low interface impedance, and long cycling.

[0041] The type of functional additives can be selected according to the application scenario of batteries containing solid electrolytes. Large energy storage batteries focus on safety and mechanical strength, and only inorganic fillers can be added. High-voltage batteries adapted to ternary and lithium-rich manganese bases focus on cycle stability and can be compounded with interface modifiers and film-forming additives. The residual solvent comes from the lithium salt activation process. The content of residual solvent can be finely adjusted by adjusting the vacuum drying temperature and drying time. A small amount of residual solvent can soften the polysaccharide molecular chain and reduce the resistance to lithium ion migration.

[0042] In some embodiments, the mass ratio of the polysaccharide matrix, lithium salt, inorganic filler, interface modifier, film-forming additive and residual solvent is (30~45):(15~25):(15~25):(5~10):(10~18):(5~10).

[0043] In solid electrolytes, when the polysaccharide matrix content is below 30 parts, the organic network framework is insufficient, and fillers and additives disperse and agglomerate, preventing membrane formation. When it exceeds 45 parts, the lithium salt and filler content are insufficient, leading to a significant decrease in conductivity and reinforcing effect. When the lithium salt content is below 15 parts, the system contains excessive free Li. +Insufficient concentration leads to decreased ionic conductivity; above 25 parts, lithium salt crystallization blocks ion channels. Inorganic filler below 15 parts results in weak mechanical reinforcement; above 25 parts, nanoparticle aggregation creates internal defects. Interface modifier below 5 parts prevents the formation of a continuous SEI film; above 10 parts, organic molecules block ion channels. Film-forming additive below 10 parts causes cyclic interface protection failure; above 18 parts, excessive gas generation during charge and discharge. Residual solvent below 5 parts results in hardened molecular chains and high ion migration resistance; above 10 parts, the film softens and lacks puncture resistance. By limiting the mass ratio of each component in the solid electrolyte within the above ranges, the components are matched and balanced, avoiding performance defects caused by excessively high or low proportions of a single material, achieving a synergistic optimal balance of mechanical strength, ionic conductivity, interface stability, and cycle life.

[0044] The mass ratio of polysaccharide matrix, lithium salt, inorganic filler, interface modifier, film-forming additive, and residual solvent includes, but is not limited to, 30:15:15:5:10:5, 32:17:17:6:12:6, 34:19:19:7:13:7, 36:20:20:7:14:7, 38:21:21:8:15:8, 40:22:22:8:16:8, 42:23:23:9:17:9, and 45:25. :25:10:18:10, 31:16:16:5:11:5, 33:18:18:6:12:6, 35:20:20:7:13:7, 37:21:21:8:14:8, 39:22:22:8:15:8, 41:23:23:9:16:9, 43:24:24:9:17:9, 35:22:18:7:15:8, 40:20:20:8:14:8. When only two types of additives are selected, the mass fractions corresponding to the unused additives can be allocated to the polysaccharide matrix or lithium salt component, while the remaining components still strictly adhere to the corresponding numerical range limits.

[0045] In some embodiments, the inorganic filler includes at least one of nano-alumina, nano-silica, and LLZO nanoparticles. Nano-alumina and nano-silica are high-rigidity inorganic particles that fill the pores of the polysaccharide network, simply improving the tensile strength of the solid electrolyte; LLZO nanoparticles have both mechanical reinforcement and lithium-ion conduction functions, which can simultaneously improve the mechanical strength of the solid electrolyte and inhibit lithium dendrite growth.

[0046] In some embodiments, the interface modifier includes at least one of vinyl ethylene carbonate (VEC) and vinylene carbonate (VC). The interface modifier molecules contain unsaturated carbonate double bonds and preferentially polymerize on the lithium metal anode surface to form a flexible SEI film, which can improve the compatibility of the electrolyte-electrode interface and reduce interfacial impedance.

[0047] In some embodiments, the film-forming additive includes at least one of fluorobenzene and vinyl sulfate. Fluorobenzene and vinyl sulfate decompose upon charge-discharge to generate a dense passivation layer containing fluorine and sulfur, which isolates the electrode from side reactions with lithium salt and solvent, thereby improving cycle life.

[0048] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), lithium difluoroborate oxalate (LiDFOB), and lithium bis(oxalate borate) (LiBOB). Lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide have wide electrochemical windows, suitable for high-voltage 4.8V cathode materials; lithium hexafluorophosphate is suitable for lithium iron phosphate and conventional ternary voltage systems; lithium tetrafluoroborate, lithium difluoroborate oxalate, and lithium bis(oxalate borate) can improve the stability of the SEI film on the electrode surface; the combination of multiple lithium salts can simultaneously achieve high ionic conductivity and long-term cycle stability.

[0049] In some embodiments, the residual solvent includes at least one of ethylene carbonate, dimethyl carbonate, propylene carbonate (PC), γ-butyrolactone (GBL), and fluoroethylene carbonate (FEC). The carbonate mixed solvent is highly polar and can efficiently dissociate lithium salts, increasing the concentration of free lithium ions in the system. Propylene carbonate, γ-butyrolactone, and fluoroethylene carbonate can serve as co-solvents; the fluorinated groups in fluoroethylene carbonate can assist in constructing a stable SEI film, broadening the electrochemical stability window of the system. After vacuum drying, a small amount of solvent remains inside the solid electrolyte, softening the polysaccharide molecular chains and reducing lithium ion migration resistance.

[0050] Furthermore, the tensile strength of the solid electrolyte is 2-4 MPa, and the ionic conductivity at 25-30℃ is 1.2 × 10⁻⁶. -3 ~2.5×10 -3 S / cm, with an electrochemical stability window of over 4.8V.

[0051] Furthermore, one embodiment of this application provides a method for preparing a solid electrolyte, comprising the following steps: (1) Disperse the polysaccharide compound in deionized water. The xanthan gum and konjac glucomannan in the polysaccharide compound are in a mass ratio of 1:(1.2~1.8). Stir at 60~70℃ until completely dissolved to obtain a uniformly mixed polysaccharide solution with a total solid content of 3%~6%.

[0052] (2) After degassing the above polysaccharide solution, pour it into a mold and keep it at 60~70℃ for 1~2h. Xanthan gum undergoes a helical-random coil conformational transformation and forms an interpenetrating three-dimensional network with konjac glucomannan chains through hydrogen bonding. After naturally cooling to 25~30℃, a hydrogel is obtained. This physical cross-linking process does not require the introduction of any chemical cross-linking agent and retains the fully biodegradable characteristics of natural polysaccharides.

[0053] (3) The obtained hydrogel is immersed in a phosphorylation reaction solution composed of phosphate, citric acid, and deionized water, wherein the phosphate concentration is 0.2~0.5 mol / L, the citric acid concentration is 0.05~0.15 mol / L, the pH is adjusted to 4~5.5, and the reaction is carried out at 80~90℃ for 0.5~4 h. The ratio of monophosphate to diphosphate is controlled by the concentration of citric acid. Citric acid, as a pH buffer and complexing agent, can precisely control the active sites of the phosphorylation reaction and achieve directional control of the ratio of the two phosphate groups. When the pH of the phosphorylation reaction solution is <4, the phosphate mainly exists in the form of H3PO4, which will inhibit the esterification reaction between the phosphate group and the polysaccharide hydroxyl group, resulting in insufficient cross-linking, decreased mechanical strength, and difficulty in effectively inhibiting lithium dendrites. When the pH is >5.5, the HPO4 in the phosphate 2- and PO4 3- As the proportion increases, the phosphorylation reaction activity is enhanced, the reaction rate is too fast, leading to excessive diesterization and cross-linking, which restricts molecular chain movement, blocks ion transport channels, and reduces ionic conductivity.

[0054] (4) After the reaction is complete, the hydrogel is taken out and repeatedly soaked and washed with deionized water to remove unreacted reagents. Then it is soaked in 0.5~2mol / L lithium salt solution for 12~24 h to activate it. Finally, it is dried in a vacuum drying oven at 60~80℃ to constant weight to obtain phosphorylated modified polysaccharide solid electrolyte.

[0055] The preparation method of this invention uses all-natural polysaccharides as raw materials, without the need to introduce synthetic polymers or toxic crosslinking agents. The preparation process is green and environmentally friendly, and the resulting electrolyte is completely biodegradable, avoiding the environmental burden of traditional synthetic polymer electrolytes.

[0056] Specifically, in step (4), citric acid is a tribasic weak acid with three dissociation constants: pKa1 = 3.13, pKa2 = 4.76, and pKa3 = 6.40. As a pH buffer, citric acid dissociates as H₂Citrate in the pH range of 4 to 5.5. − and HCit 2− It exists in the form of a buffer pair, which can effectively stabilize the pH of the reaction system. The pH of the reaction system is stabilized at 4–5.5.

[0057] If the amount of citric acid in the phosphorylation reaction solution is increased, the concentration of the citric acid buffer pair in the reaction system increases, and the pH of the reaction system tends to be close to the pKa2 (4.76) of citric acid, maintaining a relatively low pH environment. This results in a decrease in the concentration of H2PO4 in the phosphate. − The phosphorylation reaction is dominant, with moderate reactivity, which favors the formation of MPE (mainly monoesterification). If the amount of citric acid in the phosphorylation reaction solution is reduced, the buffering capacity weakens, and the pH of the reaction system increases due to the hydrolysis of phosphate itself, leading to HPO4... 2− An increased proportion enhances the activity of phosphorylation, which is beneficial for the formation of DPE (increased diesterization ratio).

[0058] Citric acid, acting as a complexing agent, competitively reacts with the hydroxyl groups of polysaccharides against phosphate, thus regulating the reactive sites. The citric acid molecule contains three -COOH groups and one hydroxyl group (-OH). The phosphate used in the phosphorylation reaction system introduces sodium (Na₂O) into the solution. + Ca 2+ Mg 2+ In plasma phosphorylation reactions, increasing the amount of citric acid in the solution leads to the complexation of more metal ions, reducing the competitive binding between metal ions and phosphate groups, and allowing more phosphate groups to react with the hydroxyl groups of the polysaccharide. Conversely, decreasing the amount of citric acid in the solution increases the number of free metal ions, resulting in some phosphate groups being occupied by metal ions and reducing the number of esterification reaction sites.

[0059] From the perspective of reactive sites, when the amount of citric acid in the phosphorylation reaction solution is high, a large number of citric acid molecules are adsorbed / bound on the surface of the polysaccharide molecular chain, creating steric hindrance to the polysaccharide hydroxyl groups. This makes it difficult for two adjacent phosphate groups to simultaneously undergo diesterylation with adjacent hydroxyl groups, thus hindering DPE formation and relatively increasing the proportion of MPE. When the amount of citric acid in the phosphorylation reaction solution is low, the steric hindrance decreases, and more adjacent hydroxyl groups on the polysaccharide molecular chain can be phosphorylated, increasing the proportion of DPE.

[0060] From the perspective of competitive reaction regulation, the hydroxyl and carboxyl groups contained in citric acid can competitively esterify with phosphates under conditions of 80-90℃. When the amount of citric acid in the phosphorylation reaction solution is high, some phosphates react with citric acid, reducing the total amount of phosphates reacting with polysaccharides, thus lowering the overall degree of phosphorylation. However, the diesterization reaction requires more phosphate groups and is more significantly affected, therefore the DPE ratio decreases. When the amount of citric acid in the phosphorylation reaction solution is low, more phosphates react with polysaccharides, and the DPE ratio increases.

[0061] Citric acid achieves directional regulation of the MPE and DPE ratio through the synergistic effects of the above aspects. As a pH buffer, it maintains the system in the optimal acidity range and controls the competitive balance of the two esterification reactions through pH fine-tuning. As a metal ion complexing agent, it exposes the active sites of polysaccharide hydroxyl groups. At the same time, it inhibits or promotes the occurrence of diesterization reactions at the molecular scale by utilizing steric hindrance and competitive reactions.

[0062] Further, the phosphate mentioned in step (3) is at least one of disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, sodium hexametaphosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

[0063] Further, the lithium salt mentioned in step (4) is at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), lithium difluoroborate oxalate (LiDFOB), and lithium bis(oxalate borate) (LiBOB). The solvent in the lithium salt solution is a mixed solvent of ethylene carbonate and dimethyl carbonate, or one or more of propylene carbonate (PC), γ-butyrolactone (GBL), and fluoroethylene carbonate (FEC) are added as a co-solvent. The proportion of co-solvent added is 10% to 30% of the mass of the lithium salt solution.

[0064] Furthermore, 0.1% to 2% of functional additives may be added to the activated lithium salt solution, wherein the amount of inorganic filler added is 0.5% to 2%, the amount of interface modifier added is 0.1% to 1%, and the amount of film-forming additive added is 0.2% to 1.5%.

[0065] An embodiment of the present invention also provides a battery comprising a solid electrolyte as described above.

[0066] Furthermore, the battery also includes a negative electrode and a positive electrode. The negative electrode includes a lithium metal negative electrode, a silicon-carbon negative electrode, or a graphite negative electrode. The positive electrode includes a positive electrode material, which includes at least one of lithium iron phosphate, ternary materials, lithium cobalt oxide, or lithium-rich manganese-based materials.

[0067] The present invention will be further illustrated by the following examples.

[0068] The solid electrolyte and battery disclosed in this invention will be described in detail.

[0069] Example 1 1. The preparation method of solid electrolyte is as follows: Weigh 49.7g of Na2HPO4 and dissolve it in 80mL of deionized water. Stir until completely dissolved, adjust the pH to 4.80 with citric acid, and bring the volume to 100mL to obtain the phosphorylation reaction solution. The concentration of Na2HPO4 in the reaction solution is 0.35mol / L, and the concentration of citric acid is 0.1mol / L.

[0070] Xanthan gum and konjac glucomannan were dispersed in deionized water at a mass ratio of 1:1.5 and stirred at 60-70°C until completely dissolved to obtain a homogeneous polysaccharide solution with a total solid content of 4%.

[0071] After degassing the polysaccharide solution, it was poured into a mold and kept at a constant temperature of 65°C for 1 hour. Then, it was naturally cooled to 25°C to obtain a hydrogel.

[0072] The prepared 10g hydrogel was immersed in 100mL of phosphorylation reaction solution, ensuring complete submersion, and reacted in a constant temperature water bath at 85℃ for 2.5h.

[0073] The hydrogel was removed and repeatedly washed with deionized water to remove unreacted reagents, yielding a phosphorylated polysaccharide matrix. It was then activated by immersion in a 1 mol / L LiPF6 solution for 18 h, and finally dried at 70 °C in a vacuum drying oven to constant weight, yielding a phosphorylated polysaccharide-based solid electrolyte.

[0074] The polysaccharide matrix contains a 2:1 molar ratio of phosphate monoester groups to phosphate diester groups. The LiPF6 solution is a 1:1 volume ratio of ethylene carbonate and dimethyl carbonate as solvent.

[0075] 2. The negative electrode is a lithium metal negative electrode.

[0076] 3. The battery manufacturing method is as follows: The negative electrode, solid electrolyte, and NCM811 positive electrode are stacked and assembled into a battery.

[0077] Examples 2-34 Examples 2-34 are largely the same as Example 1, except that they use the formulations in Tables 1 and 2.

[0078] Comparative Examples 1-4 Most of the steps in Comparative Examples 1-4 are the same as those in Example 1, except that the formulations in Tables 1 and 2 are used.

[0079] Table 1 Table 2 The solid electrolytes and batteries prepared in the above embodiments and comparative examples were tested as follows.

[0080] 1. Tensile strength of solid electrolytes: The solid electrolytes obtained in the examples and comparative examples were tested according to ASTM D882 standard. Thin film standard: the sample strip width was 10 mm, the gauge length was 50 mm, the actual measured thickness was (average of three points on a micrometer), and the testing speed was 50 mm / min.

[0081] 2. Ionic conductivity of solid electrolyte at 25℃: First, the thickness L of the prepared solid electrolyte membrane sample was measured, and the area of ​​the electrolyte sample was calculated. Next, the sample was sandwiched between two stainless steel discs to assemble an SS|electrolyte membrane|SS blocking cell. Then, the blocking cell was connected to an electrochemical workstation, and the frequency range was set to 10. -2 ~10 5 The impedance value was Hz, with an amplitude of 5mV. An EIS test was performed on it at a temperature of 30℃. Then, the ionic conductivity σ was obtained by substituting the impedance value R into Formula 2, as follows: ; Where: L is the thickness of the electrolyte (cm); R is the resistance of the electrolyte (Q); S is the surface area of ​​the electrolyte (cm²). 2 ).

[0082] 3. Electrochemical Stability Window: The electrochemical reaction window was tested using linear sweep voltammetry (LSV). The electrode potential was uniformly changed, and the resulting current changes were recorded. In LSV testing, the potential was scanned unidirectionally from an initial value to a final value; this process was continuous and linear. When a redox reaction occurred at the electrode during the voltage change, the LSV curve would change significantly, thus revealing the thermodynamic information and electrochemical reaction window of the battery reaction. A Li|electrolyte membrane sample|SS half-cell was prepared by sandwiching a solid electrolyte membrane sample between a lithium sheet and a stainless steel disc. The voltage range for LSV testing was set to 2–6 V, and the scan rate was 2 mV / s.

[0083] 4. Capacity retention rate after 200 cycles at 0.2C: After the batteries of the examples and comparative examples were placed in a constant temperature test chamber at 25℃±2℃ for 1 hour, they were charged to 4.2V at 0.2C constant current and constant voltage, with a cutoff current of 0.05C; they were then discharged to 2.75V at 0.2C constant current, and the discharge capacity was recorded; the above steps were repeated 200 times, and the capacity retention rate was calculated.

[0084] 5. Capacity retention rate after 1000 cycles at 1C: After placing the batteries of the examples and comparative examples in a constant temperature test chamber at 25℃±2℃ for 1 hour, charge them to 4.2V at 1C constant current and constant voltage, and cut off the current at 1C; discharge them to 2.75V at 1C constant current and record the discharge capacity; repeat the above steps 1000 times and calculate the capacity retention rate.

[0085] The test results are shown in Table 3.

[0086] Table 3 As shown in Table 3, the test results of each example and Comparative Examples 1-4 indicate that in Comparative Example 1, the molar ratio of phosphate monoester to phosphate diester is less than 1:1, resulting in insufficient covalent cross-linking sites, a loose three-dimensional polysaccharide network, a significant decrease in the tensile strength of the solid electrolyte, an inability to effectively suppress lithium dendrites, a narrowing of the electrochemical stability window, and a significant decrease in the battery's capacity retention rate at 0.2C and 1000 cycles of 1C. In Comparative Example 2, the molar ratio of phosphate monoester to phosphate diester is greater than 3:1, resulting in excessively high cross-linking density that blocks lithium-ion transport channels, a significant decrease in ionic conductivity, and a marked reduction in discharge specific capacity. Comparative Example 3 does not contain xanthan gum, and Comparative Example 4 does not contain konjac glucomannan, thus failing to form a complete interpenetrating polysaccharide network framework. Consequently, the electrolyte's mechanical strength and ion conductivity deteriorate simultaneously, leading to a decrease in discharge specific capacity and long-cycle stability.

[0087] As shown in Table 3, the test results of Examples 1, 2, and 3 indicate that when the molar ratio of phosphate monoester groups to phosphate diester groups is controlled within the range of (1~3):1, the phosphate diester provides covalent cross-linking to enhance mechanical strength, while the phosphate monoester provides lithium ion dissociation sites to ensure ion conduction. The tensile strength of the solid electrolyte remains at 2.2~3.8 MPa, and the ionic conductivity can reach 1.3 × 10⁻⁶ MPa. -3 ~2.2×10 -3 S / cm, electrochemical stability window ≥4.8V, battery discharge specific capacity and cycle retention rate are both at a relatively good level.

[0088] As shown in Table 3, the test results of Examples 1 and 4-7 indicate that when the molar ratio of polysaccharide matrix to modified groups is in the range of 1:(0.15-0.30), the tensile strength of the solid electrolyte is 2.8-3.5 MPa, and the ionic conductivity is 1.5×10⁻⁶ MPa. -3 ~1.9×10 -3 The battery exhibits excellent overall performance, with an electrochemical stability window ≥4.8 V, a discharge specific capacity ≥158 mAh / g, a capacity retention rate ≥89% after 200 cycles at 0.2C, and a capacity retention rate ≥75% after 1000 cycles at 1C. However, when the molar ratio is below 1:0.15 (Example 7, 1:0.1), insufficient modified groups and a low degree of phosphorylation crosslinking result in a tensile strength reduced to 1.5 MPa, failing to effectively suppress lithium dendrites and significantly decreasing battery cycle stability. Conversely, when the molar ratio is above 1:0.30 (Example 5, 1:0.5), excessive phosphorylation leads to an excessively high covalent crosslinking density, severely blocking ion transport channels and causing a sharp drop in ionic conductivity to 0.5 × 10⁻⁶. -3The discharge specific capacity was reduced to 142 mAh / g by controlling the molar ratio of polysaccharide matrix to modified groups within the range of 1:(0.15~0.30) and forming a bilayer synergistic regulation with the MPE:DPE molar ratio of (1~3):1, which can simultaneously achieve synergistic optimization of mechanical strength and ionic conductivity.

[0089] As shown in Table 3, when the total mass content of xanthan gum and konjac glucomannan in the polysaccharide matrix is ​​60% to 95%, a continuous and complete three-dimensional network skeleton can be formed, and the mechanical properties and ion conduction properties of the solid electrolyte are balanced. When the total content of the two is less than 60% or the amount of a single functional polysaccharide added exceeds 30%, the proportion of the main network structure decreases, the tensile strength decreases, the electrochemical window narrows, and the battery cycle life decreases.

[0090] As shown in Table 3, when the mass ratio of xanthan gum to konjac glucomannan is controlled within the range of 1:(1.2~1.8), the molecular chains of rigid xanthan gum and flexible konjac glucomannan are conformally matched, forming a dense hydrogen bond network, and the electrolyte has both tensile strength and ion transport capability. When the ratio deviates from this range, the system becomes too brittle or the skeleton support is insufficient, the tensile strength decreases, and the battery capacity and cycle stability decrease.

[0091] As can be seen from the test results of Examples 1, 18 to 21 in Table 3, when the mass ratio of polysaccharide matrix to lithium salt falls within the range of (30~45):(15~25), the lithium salt is fully dissociated to provide sufficient free lithium ions, and the polysaccharide skeleton ensures the mechanical strength of the membrane. If the proportion of polysaccharide matrix is ​​too high, there will be insufficient free lithium ions and the ionic conductivity will decrease. If the proportion of lithium salt is too high, lithium salt crystallization will easily occur, blocking the ion channels and reducing the tensile strength of the electrolyte and the cycle performance of the battery.

[0092] As can be seen from the test results of Examples 22 to 25 in Table 3, when the amount of inorganic filler added is controlled within the range of 15 to 25 parts, the rigid nanoparticles fill the pores of the polysaccharide network and simultaneously improve the tensile strength of the electrolyte and the lithium-ion conductivity. Insufficient filler addition results in a weak reinforcing effect, while excessive filler can easily cause particle agglomeration and reduce ionic conductivity.

[0093] As can be seen from the test results of Examples 26 to 29 in Table 3, when the amount of interface modifier added is controlled within the range of 5 to 10 parts, a uniform SEI film can be generated at the electrode interface and the interface impedance can be reduced; if the amount added is insufficient, a continuous passivation film cannot be formed, and excessive organic molecules will block some ion transport channels, resulting in a decrease in battery cycle retention rate.

[0094] As can be seen from the test results of Examples 31 to 34 in Table 3, when the amount of film-forming additive is controlled in the range of 10 to 18 parts, a stable fluorine-containing and sulfur-containing passivation layer can be formed during the charge and discharge process, which can suppress electrode side reactions and extend cycle life. If the amount of additive is insufficient, the interface protection will fail, and if the amount of additive is excessive, the gas generation during charge and discharge will increase and the battery discharge specific capacity will decrease.

[0095] As shown in Table 3, the test results of Examples 1-17 and Examples 22-34 indicate that when the mass ratio of polysaccharide matrix, lithium salt, inorganic filler, interface modifier, film-forming additive, and residual solvent is controlled within the range of (30-45):(15-25):(15-25):(5-10):(10-18):(5-10), the components mutually balance and synergistically enhance each other, resulting in a stable tensile strength of the solid electrolyte at 2-4 MPa and an ionic conductivity of 1.2 × 10⁻⁶ at 25°C. -3 ~2.5×10 -3 The S / cm ratio is improved, the electrochemical stability window reaches above 4.8V, the battery discharge specific capacity is improved, and the capacity retention rate during 0.2C and 1C long cycles is significantly improved.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that, The solid electrolyte includes a polysaccharide matrix, which includes xanthan gum and konjac glucomannan. The polysaccharide matrix also includes modifying groups, which include phosphate monoester groups and phosphate diester groups, with a molar ratio of phosphate monoester groups to phosphate diester groups of (1~3):

1.

2. The solid electrolyte according to claim 1, characterized in that, The polysaccharide matrix is ​​prepared from a raw material composition including xanthan gum, konjac glucomannan and a phosphorylation reaction solution, wherein the pH of the phosphorylation reaction solution is 4-5.

5.

3. The solid electrolyte according to claim 2, characterized in that, The phosphorylation reaction solution includes phosphate and citric acid.

4. The solid electrolyte according to claim 3, characterized in that, The phosphate includes at least one of disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, sodium hexametaphosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

5. The solid electrolyte according to claim 1, characterized in that, The mass ratio of xanthan gum to konjac glucomannan is 1:(1.2~1.8).

6. The solid electrolyte according to claim 1, characterized in that, The molar ratio of the polysaccharide matrix to the modified group is 1:(0.15-0.30).

7. The solid electrolyte according to any one of claims 1 to 6, characterized in that, The polysaccharide matrix also includes functional polysaccharides, which include at least one of sodium alginate, carboxymethyl cellulose, chitosan, guar gum, and hyaluronic acid.

8. The solid electrolyte according to claim 7, characterized in that, The total mass ratio of xanthan gum and konjac glucomannan to the mass ratio of the functional polysaccharide is (60~95):(5~40).

9. The solid electrolyte according to claim 1, characterized in that, The solid electrolyte further includes lithium salt, functional additives and residual solvent, wherein the functional additives include at least one of inorganic fillers, interface modifiers and film-forming additives; The mass ratio of the polysaccharide matrix, lithium salt, inorganic filler, interface modifier, film-forming additive and residual solvent is (30~45):(15~25):(15~25):(5~10):(10~18):(5~10).

10. A battery, characterized in that, Includes the solid electrolyte as described in any one of claims 1 to 9.